2017
DOI: 10.1111/jjns.12160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a hospital–community partnership transitional program in patients with coronary heart disease in Chengdu, China: A randomized controlled trial

Abstract: This study is an original effort to establish and evaluate a hospital-community partnership transitional care program in patients with coronary heart disease in China and the findings have demonstrated its effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 27 publications
0
24
0
2
Order By: Relevance
“…As a result, patients in the intervention group showed significantly better understanding of the importance of medication adherence and improved medication adherence 41. Similarly, in the study conducted by Zhao et al ,42 Cao et al ,43 and Zhao and Wong,44 healthcare providers gave medical directions and explained the importance of taking cardioprotective medications to patients. The result was that the medication adherence rate was higher in the pharmaceutical care group 42…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…As a result, patients in the intervention group showed significantly better understanding of the importance of medication adherence and improved medication adherence 41. Similarly, in the study conducted by Zhao et al ,42 Cao et al ,43 and Zhao and Wong,44 healthcare providers gave medical directions and explained the importance of taking cardioprotective medications to patients. The result was that the medication adherence rate was higher in the pharmaceutical care group 42…”
Section: Resultsmentioning
confidence: 93%
“…In the programme, family physicians and home nurses made structured telephone calls after patient discharge to reinforced health self-management behaviours and remind timely outpatient visits to hospital, whereas patients in the control group received routine care. Cao et al 43 found that the intervention group had significantly higher medication adherence scores than the control group at 30 days and 90 days after discharge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The registration status of five included trials was indeterminate (Cao, Tian, Chen, & Jiang, ; Cobbing, Hanass‐Hancock, & Myezwa, ; Jensen, Kiesbye, Soendergaard, Jensen, & Kristensen, ; Salameh et al, ; Valiee, Razavi, Aghajani, & Bashiri, ). When we checked the registration status of the Cobbing et al () trial, the registration number in the paper was not listed in the registry (South African National Clinical Trials Registry).…”
Section: Resultsmentioning
confidence: 99%
“…Patient involvement with individualized discharge plans and the clear identification and setting of treatment goals can facilitate initiation and implementation of the treatment regimen. Finally, regularly scheduled (monthly) telephone or in‐person follow‐up visits with pharmacists, nurses, health care counselors, or physicians to review goals, reconcile medications, identify and address adverse effects and other hinderances, and provide and reinforce patient education may further improve medication adherence …”
Section: Introductionmentioning
confidence: 99%